Biokimyo fanini o‘qitishda keys usulini qo‘llash masalalari (SCIENCE and SOCIETY, 2020)
The article provides theoretical information and practical recommendations on the use of the case study in teaching biochemistry in higher medical education, as well as on the use of cases in the classroom and assessment of students‘ knowledge. It was found that the use of case studies in the learning process develops students‘ practical skills and creativity.